Viral Infection: A Potent Barrier to Transplantation Tolerance. (14th September 2008) - Miller, David M.; Thornley, Thomas B.; Greiner, Dale L.; Rossini, Aldo A.
Abstract : Transplantation of allogeneic organs has proven to be an effective therapeutic for a large variety of disease states, but the chronic immunosuppression that is required for organ allograft survival increases the risk for infection and neoplasia and has direct organ toxicity. The establishment of transplantation tolerance, which obviates the need for chronic immunosuppression, is the ultimate goal in the field of transplantation. Many experimental approaches have been developed in animal models that permit long-term allograft survival in the absence of chronic immunosuppression. These approaches function by inducing peripheral or central tolerance to the allograft. Emerging as some of the most promising approaches for the induction of tolerance are protocols based on costimulation blockade. However, as these protocols move into the clinic, there is recognition that little is known as to their safety and efficacy when confronted with environmental perturbants such as virus infection. In animal models, it has been reported that virus infection can prevent the induction of tolerance by costimulation blockade and, in at least one experimental protocol, can lead to significant morbidity and mortality. In this review, we discuss how viruses modulate the induction and maintenance of transplantation tolerance.